Kinetics of Formation and Growth of Microdefects in Crystals - S. J. Olikhovsky, M. M. Belova, Ye. V. Kochelab (Успехи физики металлов, 2006)
In the review, the main results of numerous direct observations of microdefects’ formation (oxygen precipitates and dislocation loops) in a silicon crystal during its growth and heat treatments are described. Thermodynamic conceptions concerning formation of new-phase particles in the supersaturated solid solution of oxygen in silicon are briefly presented. Classical approaches to the description of oxygen-precipitation kinetics are represented too. Modern models of kinetics of growth and decomposition of precipitates and dislocation loops in silicon are described.